The Exponential Generating Functions of Mersenne and Mersenne-Lucas Identities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we presented some relations connecting Mersenne and Mersenne-Lucas sequences by applying exponential generating functions.